The answer is: " - 49" .
______________________________________________
" f(2) = 49 " .
______________________________________________
Step-by-step explanation:
______________________________________________
Given: " f(x) = x – 51 " ; Find " f(2) " ;
→ Plug in "2" for "x" to solve for " f(2)" ;
→ f(2) = 2 – 51 = - 49 ;
______________________________________________
The answer is: " - 49" .
______________________________________________
" f(2) = 49 " .
______________________________________________